Corrections to “Emotion Recognition in Gaming Dataset to Reduce Artifacts in the Self-Assessed Labeling Using Semi-Supervised Clustering” - Oscar Almanza-Conejo; Juan Gabriel Avina-Cervantes; Arturo Garcia-Perez; Mario Alberto Ibarra-Manzano (IEEE Access)
Presents corrections to the paper, (Corrections to “Emotion Recognition in Gaming Dataset to Reduce Artifacts in the Self-Assessed Labeling Using Semi-Supervised Clustering”).